2020
DOI: 10.1038/s41416-020-01201-z
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib promotes antitumour immunity and shows antitumour activity in combination with PD-1 blockade in mice: potential role of cancer-associated fibroblasts

Abstract: Background Cancer-associated fibroblasts (CAFs) in the tumour microenvironment (TME) suppress antitumour immunity, and the tyrosine kinase inhibitor nintedanib has antifibrotic effects. Methods We performed a preclinical study to evaluate whether nintedanib might enhance antitumour immunity by targeting CAFs and thereby improve the response to immune checkpoint blockade (ICB). Results Whereas nintedani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
0
33
0
4
Order By: Relevance
“…Nintedanib also promotes antitumor immunity and antitumor activity in combination with PD-1 blockade in mice. 9 In conclusion, we encountered a patient with NSCLC and IPF who responded well to nintedanib. Further research is warranted for identifying predictive factors that may help in the selection of appropriate treatments for individual patients with lung cancer complicated by IPF.…”
Section: Discussionmentioning
confidence: 89%
“…Nintedanib also promotes antitumor immunity and antitumor activity in combination with PD-1 blockade in mice. 9 In conclusion, we encountered a patient with NSCLC and IPF who responded well to nintedanib. Further research is warranted for identifying predictive factors that may help in the selection of appropriate treatments for individual patients with lung cancer complicated by IPF.…”
Section: Discussionmentioning
confidence: 89%
“…VEGF also exerts direct immunosuppressive effects on numerous cell types; for example, by inhibiting dendritic cell maturation and promoting the expansion of regulatory T cells, myeloid-derived suppressor cells and tumour-associated macrophages [9,23]. The 'angio-immunogenic switch' hypothesis proposes that anti-angiogenic treatment could reverse the immunosuppressive TME that contributed initially to the failure of ICI therapy [8e10], and this is supported by preclinical data [22,25], the efficacy results observed in this latest analysis of VARGADO cohort B and in patients treated with nintedanib plus docetaxel in the second line, following first-line chemotherapy plus ICIs in VARGADO cohort C [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent retrospective analysis investigated the efficacy of third-line ramucirumab plus docetaxel after failure of first-line chemotherapy and second-line ICI therapy (n ¼ 67); ORR was 36%, DCR was 69%, median PFS was 6.8 months and median overall survival was 11.0 months after the start of third-line treatment [6]. Preclinical data indicate potential synergies stemming from the combination of ICIs with antiangiogenic agents [25]. Many clinical trials are underway investigating such combinations in NSCLC, and early data are encouraging [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Haratani et al, the authors inoculated s.c. B16-F10 cells in C57BL/6 mice. They demonstrated that the oral administration of nintedanib markedly delayed tumor growth (around three-fold) and prolonged mice survival when compared to control [187]. Using the same tumor induction protocol, Ferreira and coworkers demonstrated that indomethacin incorporated in mesoporous silica nanoparticles inhibited tumor growth by up to 70%.…”
Section: Syngeneic Modelmentioning
confidence: 99%